Penerapan Aplikasi E-Kasir dalam Manajemen Usaha kecil dan Menengah - Afdhal Syafnur; Edi Kurniawan; Riki Andri Yusda (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
In today's technological era, business actors can no longer be separated from the role of computers. Small and Medium Enterprises is a business that is built on individual ideas that exist in a community environment. In this case, small and medium enterprises also play a very important role in the economy and participate in helping the government. One of the small and medium enterprises in Dusun 2 Desa Ofa Padang Mahondang management still uses conventional methods in its books, such as information on goods data, transactions and financial reports so that there are various problems faced in calculating the amount of stock of goods, goods sold and financial reports that are not balanced. E-Kasir is an application that can help perpetrators in managing these problems in monitoring data on goods, stock of goods, goods sold, transaction reports. As for the expected results in this community service, small and medium business actors in Dusun 2 Desa Ofa Padang Mahondang can apply E-Kasir as a supporting application of daily operations and help solve existing problems.